Оптимізація параметрів світлопрозорих конструкцій - Марущак, У. Д.; Позняк, О. Р.; Солтисік, Р. А.; Проць, Є.; Marushchak, Ulyana; Poznyak, Oksana; Soltisik, Roman; Prots, Evgen (Видавництво Львівської політехніки, 2019)
Проаналізовано вплив конструктивних та теплотехнічних параметрів світлопрозорих огороджень на споживання енергії в будинку садибного типу з позицій забезпечення необхідного рівня природного освітлення та мінімізації трансмісійних втрат. Проведено оптимізацію теплотехнічних параметрів огороджувальних світлопрозорих конструкцій будинку для забезпечення енергетичних показників у напрямку створення енергоефективного будинку за параметрами опору теплопередачі та раціональної площі. Показано, що трансмісійні втрати можуть змінюватися в межах 1000–3800 кВт. год/рік за варіювання вибраних параметрів вікон. Здійснено перевірку вибраної моделі світлопрозорих конструкцій на відповідність вимогам теплової надійності. На основі аналізу енергетично-екологічних показників будинку методом математичного моделювання запропоновано систему оцінювання впливу будівельних об’єктів на довкілля.

The influence of structural and thermal parameters of window structures on energy consumption in a house of a residential type is analyzed in this article from the standpoint of providing the required level of natural lighting and minimizing of transmission losses. It was shown, that modern buildings are characterized by a much larger proportion of the area of window structures, which requires a special analysis of the effect of translucent enclosures on the energy performance of buildings. The window structures should provide harmonious natural lighting of the rooms, while protecting them from external noise, temperature fluctuations, intense solar radiation and other negative factors. The classification of window blocks by the parameter of the thermal resistance was presented. Window structures with different levels of thermal resistance parameter in accordance to thermal reliability condition (τimin > tmin) were calculated. It was established that the window structures of class D1 (thermal resistance is 0.39 m2K/W) and above are characterized by an interior surface temperature higher than 6 °C, which meet the standard requirements. The thermal parameters of window structures have been optimized to provide energy performance in the direction of creating an energy-efficient building. The parameters of optimization such as thermal resistance of window structures (X1 = 0.39; 0.75; 1.11 m2. ·K/W) and geometric parameter corresponding to the ratio of the area of window to the floor area (X2 = 1:6, 1:7 1:8) were chosen. For a residential house with a minimum allowable area of window structures in terms of natural lighting and maximum thermal resistance, the minimum level of heat loss is reached 1026.40 kW·h/year, and CO2 emissions – 248 kg/year, heat losses and greenhouse gas emissions decrease by 3.7 times compared to the calculation model. It was established that the smallest heat losses occur through energy efficient windows (thermal resistance is 1.11 m2 ·K/W) with the ratio of the area of window structures to the floor area of the room, which equal 1:8
Optimization of parameters of illuminated structures
Keywords: світлопрозора конструкція; тепловтрати; опір теплопередачі; енергоефективність; heat loss; thermal resistance; energy efficiency